NETosis of Peripheral Neutrophils Isolated From Dairy Cows Fed Olive Pomace - Ciliberti, Maria Giovanna; Albenzio, Marzia; Claps, Salvatore; Santillo, Antonella; Marino, Rosaria; Caroprese, Mariangela (Frontiers in Veterinary Science, 2021)
Neutrophils represent primary mobile phagocytes recruited to the site of infection, and their functions are essential to enhance animals' health performance. Neutrophils have an essential role in innate immunity and are able to kill the pathogens via the synthesis of neutrophil extracellular traps (NETs). The objective of the present work was the study of the in vitro NETosis of peripheral neutrophils isolated from dairy cows supplemented with olive pomace. Dairy cows (n = 16) balanced for parity (3.67 ± 1.5 for CON, 3.67 ± 1.9 for OP), milk yield (24.3 ± 4.5 kg d−1for CON and 24.9 ± 1.7 kg d−1 for OP), the number of days in milk (109 ± 83.5 for CON and 196 ± 51 for OP), and body weight (647 ± 44.3 kg for CON and 675 ± 70.7 kg for OP) were divided into two experimental groups fed with a control diet (CON) and supplemented with 6% of olive pomace (OP). Peripheral blood neutrophils were isolated and stimulated in vitro with phorbol-myristate-acetate (PMA) as a marker for activation and reactivity of the neutrophils. After isolation, both the viability and CD11b expression were analyzed by flow cytometry. Both NETosis by neutrophil elastase-DNA complex system and myeloperoxidase (MPO) activity were evaluated by ELISA. The specific antibodies against MPO and citrullination of Histone-H1 were used for investigating NETosis by immunofluorescence microscopy. The neutrophil elastase-DNA complexes produced during NETosis and MPO activity of neutrophil extracts were affected by OP supplementation. Furthermore, results from immunofluorescence analysis of NETosis depicted a similar result found by ELISA showing a higher expression of MPO and citrullination of Histone-H1 in OP than the CON neutrophils. In addition, all data showed that the OP diet resulted in a better response of neutrophils to PMA stimulation than the CON diet, which did not support the neutrophils' responses to PMA stimulation. Our results demonstrated that OP supplementation can enhance the neutrophil function in dairy cows leading to udder defense and inflammation response especially when an immunosuppression state can occur.